2015
DOI: 10.1007/s12221-015-4624-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and adsorption behavior of diethylenetriamine/polyacrylonitrile composite nanofibers for a direct dye removal

Abstract: The diethylenetriamine (DETA)/polyacrylonitrile (PAN) composite nanofibers were prepared by using electrospinning technique. The surface morphology and chemical characterization of PAN/DETA composite nanofibers were investigated using scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy. Releasing possibility of DETA from nanofibers was tested by total organic carbon (TOC) analysis. Results indicated that the incorporation of DETA into PAN affects the morphology of nanofibers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(61 citation statements)
references
References 39 publications
1
60
0
Order By: Relevance
“…25 Recently, PAN surface modification has been performed by many researchers using diethylenetriamine, polyethyleneimine and ethylenediamine for heavy metal ions and dye adsorption. 26 It is reported that mixed metal oxides containing two or more metals were effective catalysts and catalytic supports for a wide variety of organic reactions. 27,28 Taking advantage of the high specific surface area of nanostructures, TiO 2 and other metal oxides have been utilized to enhance dye degradation adsorption purpose.…”
Section: Introductionmentioning
confidence: 99%
“…25 Recently, PAN surface modification has been performed by many researchers using diethylenetriamine, polyethyleneimine and ethylenediamine for heavy metal ions and dye adsorption. 26 It is reported that mixed metal oxides containing two or more metals were effective catalysts and catalytic supports for a wide variety of organic reactions. 27,28 Taking advantage of the high specific surface area of nanostructures, TiO 2 and other metal oxides have been utilized to enhance dye degradation adsorption purpose.…”
Section: Introductionmentioning
confidence: 99%
“…The intraparticle diffusion model is given as : qt= kp t12+I where k p and I are the intraparticle diffusion rate constant (gmol −1 min −1/2 ) and intercept related to the adsorption steps, respectively. If the intraparticle diffusion is involved in the adsorption reaction, then a plot of q t against t 1/2 gave a straight line and the particle diffusion would be the controlling step if this line passed through the origin .…”
Section: Resultsmentioning
confidence: 99%
“…is chemical modification of the composite structure affected the removal efficiency of the direct dyes. Also, it is important to note that the amount of dye adsorbed had been affected by the ratio of the diethylenetriamine added to the composite, indicating how important the composition ratio is in the composite [21].…”
Section: Polymer-based Adsorbents For Dye Removalmentioning
confidence: 99%
“…SEM images of diethylenetriamine incorporated with polyacrylonitrile (a) before and (b) after surface modification (reproduced with a permission from[21]). …”
mentioning
confidence: 99%